Bishop in Honan : mission and museum in the life of William C. White - Walmsley, Lewis Calvin, 1897- (Heritage., 1974)
This volume recounts the history of the rich life of William C. White, first as a missionary in China, and then as a collector and curator of Chinese archaeology.